Surgical treatment by Videolaparoscopy versus Robotics: Influence on the survival of patients with Colorectal Cancer (Research, Society and Development, 2025)
Colorectal cancer is one of the most prevalent malignant neoplasms worldwide and represents a significant public health concern due to its high morbidity and mortality. This study aimed to compare the impact of laparoscopic and robotic surgical techniques on five-year survival in colorectal cancer patients. A retrospective observational study was conducted with 239 patients who underwent surgery between 2014 and 2020, of which 72 were excluded, at a General Surgery Service in hospitals in Rio de Janeiro. Data were collected from electronic medical records and supplemented with the National Mortality Registry, analyzed using descriptive and comparative statistics. The sample had a mean age of 66 years, a predominance of females (57%), and patients at various disease stages. Laparoscopy was the most frequently used technique (71%), followed by conventional surgery (17%) and robotic surgery (12%). Results showed that 67% of patients survived five years or more, with no statistically significant difference between the minimally invasive techniques. Laparoscopy proved to be widely accessible and effective in the Brazilian context, while robotic surgery offered functional and perioperative advantages but faced limitations in cost and availability. Future studies should examine the relationship between quality of life, cost-effectiveness, and survival to guide more equitable public health policies.